Control Technologies for Emerging Micro and Nanoscale Systems - Eleftheriou, Evangelos.; Eleftheriou, Evangelos.; Moheimani, S.O. Reza.; Moheimani, S.O. Reza. (Lecture Notes in Control and Information Sciences,, 2011)
This book comprises a selection of the presentations made at the “Workshop on Dynamics and Control of Micro and Nanoscale Systems” held at IBM Research – Zurich, Switzerland, on the 10th and 11th of December 2009. The aim of the workshop was to bring together some of the leading researchers in the field of dynamics and control of micro- and nanoscale systems. It proved an excellent forum for discussing new ideas and approaches.